Creative Writing Skills in English: Developing Student's Potential and Creativity - Tira Nur Fitria (The Study Program of English Education of Palangka Raya University, 2024)
This research describes teaching creative writing skills in English to develop student's potential and creativity. This research is library research. The finding shows that creative writing is an innovative writing style that emphasizes narrative, character development, opinions, and non-formal language styles. It involves expressing ideas and imagination in various forms of fiction and nonfiction and requires the ability to build the reader's imagination and research skills such as poetry, short stories, novels, epics, short stories, fairy tales, drama scripts, film scenarios, song lyrics, television scripts, advertising scripts, popular articles, opinions, news, etc. It also attracts attention and entertains readers, requiring the author's ability to build the reader's imagination. Creative writing in English is a rewarding activity that increases students’ creativity, trains their imagination, and improves their English skills. To improve creative writing skills, students should read diverse literary works, practice regular writing, explore different language styles, use writing prompts, and accept feedback from friends or teachers. Mastering these skills in English can lead to self-expression, imagination, language and vocabulary improvement, and effectively conveying messages. Techniques to improve creative writing skills include reading diverse literary works, practicing regular writing, exploring different language styles, using writing prompts, and being open to feedback from friends or mentors.